PENGARUH KINERJA DAN PROFESIONALISME AUDITOR: TERHADAP KUALITAS AUDIT KEUANGAN PADA KAP AIDIL OSCAR DAN REKAN (Jurnal Akuntansi, 2024)
This study examines the impact of auditor performance and professionalism on audit quality at KAP Aidil Oscar dan Rekan, both partially and simultaneously. Employing a causal research design, the study utilized primary data collected via questionnaires from a sample of 30 employees, determined through the Slovin formula. Data analysis was performed using SPSS version 28, specifically focusing on the F-test for hypothesis testing. The findings demonstrate that both auditor performance and professionalism significantly influence audit quality, confirming previous research by Arya Wardana (2022). These results suggest that firms must prioritize enhancing auditor performance and professionalism to ensure a high standard of financial audit quality.